Nucleo CMP Forte™ for the treatment and rehabilitation of patients with carpal tunnel syndrome - Sh I Magalov; SG Huseynova; EE Mustafaeva; R Bagirova (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2023)
Introduction: Carpal Tunnel Syndrome (CTS) is the most common and best well-known cause of peripheral nerve compression. To date, none of the studies have determined the optimal combination of pyrimidine nucleotides and electrical stimulation (ES) in CTS patients. The objective of the study was to evaluate the effectiveness of a novel product containing uridine and cytidine monophosphate (Nucleo CMP Forte™) in combination with ES for the treatment of CTS. Methods: This open-label, randomized, controlled study involved 60 patients with CTS at the Azerbaijan Medical University (Baku, Azerbaijan) and Research Institute of Medical Rehabilitation between 2017 and 2021 years. Patients were randomized to receive the exploratory treatment (Nucleo CMP Forte™ and ES) or single ES treatment for ten days. The combination treatment included two stages: Nucleo CMP Forte™ and ES for ten days (stage one), and Nucleo CMP Forte™ as monotherapy (stage two) for ten days. Results: In the exploratory group, the complete restoration of pain sensitivity was achieved by 17.1% of patients and the narrowing of the existing zone of hypesthesia by 74.3%. Positive Tinel test was revealed in 52.4% of patients after the first and 76.2% after the second stage in the exploratory group, versus 43.8% in the control group. Mean values in the Boston Carpal Tunnel Questionnaire significantly decreased in both groups. Conclusion: Nucleo CMP Forte™ in combination with ES contributes to a more pronounced regression of patients' complaints, clinical manifestations, severity, and neurophysiological indicators in mild-to-moderate CTS.